PENGARUH PERBEDAAN KONSENTRASI PUPUK MEDIA DIATOM DAN PUPUK KW21 TERHADAP KEPADATAN POPULASI Tetraselmis sp. DI UNIT PELAKSANA TEKNIS LOKA PENGEMBANGAN BIO INDUSTRI LAUT PUSAT PENELITIAN OCEANOGRAFI (LPBIL P2O LIPI) MATARAM - Mukminah Mukminah; Agil Al Idrus; Agus Ramdani (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2013)
The present research aims at knowing: 1) the influence of different concentration of diatom media fertilizer on the population density Tetraselmis sp.; 2) the influence of different concentration of KW21 fertilizer on the population density Tetraselmis sp.; 3) an optimal concentration of diatom media fertilizer and KW21 for the population density of Tetraselmis sp. An experimental with Completely Randomized Design was conducted by treating diatom media fertilizer and KW21 fertilizer. Each of the treatments was given concentration of 0%, 25%, 50%, 75%, and 100%. The results show that the concentration of diatom media fertilizer did give any significance influence on the population density of Tetraselmis sp. It could be seen from the value of Ftest which was lower than Ftable (23,05) > 3.48) at the significance level of 5%. The concentration of KW21 fertilizer had any significance influence on population density of Tetraselmis sp. by which the value of Ftest was 10,63 and the Ftable was 3.48 at the significance level of 5%. An optimal population density of Tetraselmis sp. fell on the treatment of A1B4C1 (94.83x105 cell/ml) and A2B4C1 (91.83x105 cell/ml).